The Relationship Duration of Sitting and Work Posture Risk with LBP in Library Staff University of Jember - Diana Eki Cahyani; Muhammad Hasan; Nindya Shinta Rumastika (Faculty of Medicine, University of Jember, 2020)
Low back pain (LBP) is one of the occupational diseases caused by non-ergonomic conditions. The global point prevalence of LBP which limits activity in 2015 was 7.3%. This figure shows that in one time there were 540 million people who experienced LBP. As many as 90% of cases of low back pain are not caused by organic abnormalities but by errors in body position at work. Risk factors that have the potential to cause complaints include age, gender, Body Mass Index (BMI), smoking habits, work period, poor work posture, and standing or sitting too long. This study aims to determine the relationship between duration of sitting and risk of work posture with the level of LBP complaints in Jember University library employees. The type of research used was analytic observational with cross sectional study design. The sampling technique is done by total sampling. The research samples were University Library staff in Jember who experienced LBP complaints and in accordance with the inclusion and exclusion criteria of this study. The sample size was 22 respondents. The instruments of this study were respondent characteristics questionnaire sheets, LBP screening sheets, and Modified Quick Exposure Check (QEC) assessment sheets. Bivariate analysis using the gamma correlation test. The results of the bivariate analysis between duration of sitting and LBP complaint rates obtained p = 0.827. The results of the bivariate analysis between the risk of work posture and LBP complaints were obtained p = 0.916. The two results of the analysis indicate that there is no significant relationship between the duration of sitting and the risk of work posture with the level of LBP complaints in Jember University library employees. Keywords: low back pain, duration of sitting, work posture, library staff